Minimal invasive periodontal surgery: a review - Sesha M. Reddy; Hossam AE. Abdelmagyd; Shishir R. Shetty; Shakeel S. Khazi; Venkata R. Vannala (Journal of Dentomaxillofacial Science, 2017)
Objective: Periodontal therapy success is dependent on proper diagnosis and removal of sub gingival tooth–borne deposits such as acquired pellicle, calculus. and bacterial plaque biofilm besides, proper case selection and patient cooperation. From clinical perspective, enhanced visualization during the diagnostic and therapeutic periods has been given away to produce better results when matched to old-style approaches. Minimally invasive periodontal therapy appraises the benefits of using minimal invasive techniques, the knowledge available for improving visualization during therapy. This review reports the benefits and drawbacks of minimally invasive periodontal surgery and validation for current approach.Methods: Keywords such as minimally invasive periodontal surgery, periodontal surgery, and regeneration was used to search in Google and PubMed. Full text articles in English that were published from 1995 to 2016 are presented. Only case and control studies and randomized clinical trials were included in this review.Results: Abstracts and articles published in other languages were not included in the review. This review makes available an evidence–based assessment of the knowledge and procedures.Conclusion: Minimally invasive periodontal surgery might be considered a true reality in the field of periodontal regeneration. Clinical improvements seen were consistently associated with very limited morbidity.